2017
DOI: 10.3390/nano7110347
|View full text |Cite
|
Sign up to set email alerts
|

Influence of VO2 Nanoparticle Morphology on the Colorimetric Assay of H2O2 and Glucose

Abstract: Nanozyme-based colorimetric sensors have received considerable attention due to their unique properties. The size, shape, and surface chemistry of these nanozymes could dramatically influence their sensing behaviors. Herein, a comparative study of VO2 nanoparticles with different morphologies (nanofibers, nanosheets, and nanorods) was conducted and applied to the sensitive colorimetric detection of H2O2 and glucose. The peroxidase-like activities and mechanisms of VO2 nanoparticles were analyzed. Among the VO2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 51 publications
(52 reference statements)
1
27
0
Order By: Relevance
“…Owing to the shape, size, and surface chemistry of nanomaterials can dramatically influence their catalytic activities. A comparative study of peroxidase‐like activity of VO 2 nanomaterials with different morphologies (nanofibers, nanosheets, and nanorods) was reported by Qi et al The peroxidase‐like activity of various VO 2 nanomaterials was investigated upon catalysis of H 2 O 2 with peroxidase substrate TMB. Results showed that the VO 2 nanofibers showed a higher affinity for H 2 O 2 than VO 2 nanosheets, VO 2 nanorods, Fe 3 O 4 MNPs, and HRP.…”
Section: Glucose Biosensormentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the shape, size, and surface chemistry of nanomaterials can dramatically influence their catalytic activities. A comparative study of peroxidase‐like activity of VO 2 nanomaterials with different morphologies (nanofibers, nanosheets, and nanorods) was reported by Qi et al The peroxidase‐like activity of various VO 2 nanomaterials was investigated upon catalysis of H 2 O 2 with peroxidase substrate TMB. Results showed that the VO 2 nanofibers showed a higher affinity for H 2 O 2 than VO 2 nanosheets, VO 2 nanorods, Fe 3 O 4 MNPs, and HRP.…”
Section: Glucose Biosensormentioning
confidence: 99%
“…The morphology and shape of nanomaterials also hold an important position in tuning their peroxidase‐like catalytic activity. In Qi's report, they synthesized vanadium dioxide nanomaterials with different morphologies (nanofibers, nanosheets, and nanorods) and compared their peroxidase‐like activities. Simultaneously, a comparative quantitative detections of glucose was done on nanofibers, nanosheets, and nanorods.…”
Section: Tunable Peroxidase‐like Activity Of Nanomaterialsmentioning
confidence: 99%
“…Aside from its peroxidase mimic, a layered V 2 O 5 2D structure was also used to detect GSH via an oxidase-type mechanism [147]. Lower valence state vanadium oxide, VO 2 was investigated in various morphologies [109]. Fibrillar, lamellar and elongated NPs were tested against TMB substrate and it was pointed out that VO 2 sheets exhibited the best kinetic overall parameters in regard of K m and v max .…”
Section: Vanadium-based Oxidesmentioning
confidence: 99%
“…The shape and morphology of nanozymes plays a key role in regulating their catalytic activity [49][50][51][52]. Tian et al have investigated the effect of different morphologies (nanosheets, nanofibers, and nanorods) of VO2 nanoparticles on the colorimetric assay for H2O2 and glucose [53]. It is found that VO2 nanofibers exhibit the highest peroxidase-like activity, since the specific surface area of VO2 nanofibers is much larger than that of VO2 nanosheets and nanorods.…”
Section: Morphologymentioning
confidence: 99%